Sediment elemental composition (XRF) of sediment core GeoB19916-6, 30 kV run - Weiser, Jens; Hebbeln, Dierk (In: Weiser, J; Hebbeln, D (2025): Sediment elemental composition (XRF) of sediment core GeoB19916-6 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.984301, 2025)
XRF Core Scanner data of sediment core GeoB19916-6 from Baffin Bay were collected every two centimetres downcore over an active area of 15 mm² with a downcore slit size of 10 mm using generator settings of 30 kV directly at the split core surface of the archive half with XRF Core Scanner II (AVAATECH Serial No. 2) at MARUM, Bremen.
Keywords: Baffin Bay; elemental composition; XRF; XRF scanning